Biomechanical considerations in slipped capital femoral epiphysis and insights into prophylactic fixation. (1st April 2017) - Leblanc, E.; Bellemore, J. M.; Cheng, T.; Little, D. G.; Birke, O.
Abstract: Purpose: Slipped capital femoral epiphysis (SCFE) is a deformity of the proximal femur secondary to widened and unstable physis. In stabilising the slip, gold standard treatments stop growth and involve premature physeal closure, which prevents the remodelling of the acquired deformity and creates a leg length discrepancy that may be significant in younger patients. Methods: We measured the impact of placing threaded screws across the proximal femoral physis by measuring the centre-trochanteric distance (CTD) and articulo-trochanteric distance (ATD) in participants with or without prophylactic fixation. We then compared the mechanical performance of static (stainless and titanium cannulated Synthes screws) and potentially growing implants (Synthes SCFE screw and Pega Medical Free Gliding screw) in a validated synthetic bone model. Results: In the review of 30 non-fixed and 60 fixated hips over a mean follow-up of 1.9 years, we have noted a significant difference in pre/post CTD and ATD, as well as the change in CTD and ATD over time. In the biomechanical study, the newer implants allowing growth (Synthes SCFE screw and Pega Medical Free Gliding screw) were both shown to be at least non-inferior. Conclusions: The primary deformity of a SCFE in itself alters hip mechanics. Also, as confirmed in this study, there is a secondary deformity that is created by static fixation and relative trochanteric overgrowth. To help remodel mild deformities and prevent secondary trochanteric overgrowth, growing implants seem to be non-inferior to the more standard means of fixation in static testing.